Pemanfaatan Bakteri Azotobacter untuk Meningkatkan Efisiensi Penggunaan Pupuk Urea pada Tanaman Padi (Oryza sativa L.) - NI MADE INDRA PUSPAWATI; KHAMDAN KHALIMI; GUSTI NGURAH ALIT SUSANTA WIRYA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Utilization of Azotobacter Bacteria to Increase the Efficiency of Urea Fertilizer Use in Rice Plants (Oryza sativa L.) Rice is a food plant in the form of grasses (Gramineae) originating from the tropical and subtropical continents of Asia and West Africa. Nearly half of the world's population, including Indonesia, uses rice as the staple food consumed to meet food needs. Based on BPS data, the population shows an increase every five years. It is inversely proportional to the decreasing total rice production. One of the efforts to improve the cultivation technology package and increase the quality of intensification is the use of Azotobacter bacteria as a biofertilizer. Based on the isolation results, 52 Azotobacter isolates were found grown on Abhys mannitol agar. Based on the results of the selection of Azotobacter bacterial isolates, it was found that four Azotobacter bacterial isolates had the best effect on root growth of rice plants, namely the Azotobacter PD3, PD23, PD48, and PD51 bacterial isolates. The test results with GC-MS showed that 2 compounds were thought to contribute to increasing the growth of rice plants. These compounds were n-Hexadecanoic acid and oleic acid, which were included in the fatty acid group. The isolates of the Azotobacter PD3, PD48, PD51 bacteria were able to increase the efficiency of using urea by 25-50%. In comparison, the PD23 bacteria were able to increase the efficiency of using urea by 25% based on the number of tillers.